FAKTOR-FAKTOR YANG MEMPENGARUHI KEANDALAN ASET BERSEJARAH (Studi Persepsi pada SMAN 2 Purwokerto) - , Irna Indriani, Dr. Wakhid Slamet Ciptono, M.B.A., M.P.M ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study which entitled Factors Affecting Reliability of Historical al Assets (Perception Studies in SMAN 2 Purwokerto), aimed to analyze the building reliability of SMAN 2 Purwokerto seen from buildings safety, buildings health, building comfort, and accessibility of construction. This study used primary and secondary data. The primary data contained a sample of 130 people